Spectroscopic and in silico investigation of the interaction between GH1 β‐glucosidase and ginsenoside Rb1. Issue 4 (9th February 2021) - Zhong, Shuning; Yan, Mi; Zou, Haoyang; Zhao, Ping; Ye, Haiqing; Zhang, Tiehua; Zhao, Changhui
Abstract: The function and application of β‐glucosidase attract attention nowadays. β‐glucosidase was confirmed of transforming ginsenoside Rb1 to rare ginsenoside, but the interaction mechanism remains not clear. In this work, β‐glucosidase from GH1 family of Paenibacillus polymyxa was selected, and its gene sequence bglB was synthesized by codon. Then, recombinant plasmid was transferred into Escherichia coli BL21 (DE3) and expressed. The UV–visible spectrum showed that ginsenoside Rb1 decreased the polarity of the corresponding structure of hydrophobic aromatic amino acids (Trp) in β‐glucosidase and increased new π‐π * transition. The fluorescence quenching spectrum showed that ginsenoside Rb1 inhibited intrinsic fluorescence, formed static quenching, reduced the surface hydrophobicity of β‐glucosidase, and KSV was 8.37 × 10 3 L/M (298K). Circular dichroism (CD) showed that secondary structure of β‐glucosidase was changed by the binding action. Localized surface plasmon resonance (LSPR) showed that β‐glucosidase and Rb1 had strong binding power which KD value was 5.24 × 10 –4 (±2.35 × 10 –5 ) M. Molecular docking simulation evaluated the binding site, hydrophobic force, hydrogen bond, and key amino acids of β‐glucosidase with ginsenoside Rb1 in the process. Thus, this work could provide basic mechanisms of the binding and interaction between β‐glucosidase and ginsenoside Rb1 . Abstract : The interaction mechanism between GH1 β‐glucosidase and ginsenoside Rb1 innovatively studied by UV, fluorescence, CD, LSPR, and molecular docking. MD simulations revealed binding sites for ginsenoside Rb1 to bind to β‐glucosidase, the hydrophobic force, hydrogen bond, and the important amino acid residues.